Prevalence of myopia among senior students in Fenghua, Eastern China, before and during the COVID-19 pandemic - Zhou, Xuewei; Liu, Tong; Wu, Aimin; Cheng, Bo; Chen, Min; Wang, Kaijun (Frontiers in Public Health, 2023)
Background Myopia is a common cause of vision impairment worldwide. In China, the prevalence, the affected population, and the onset age of myopia are prominent issues. Prevention and intervention of myopia are great public health concerns. Methods This school-based retrospective study retrieved visual acuity and refractive data of senior students (grade 12th) from six high schools in Fenghua City, Zhejiang Province, eastern China, from 2016 and 2022. Noncycloplegic autorefraction was performed for refractive status. Students were divided into three subgroups by their school types. The overall myopia prevalence, as well as the prevalence of low myopia, moderate myopia, and high myopia, were calculated separately for each year. Statistical analyzes were performed using SPSS 25.0 and Graphpad Prism software. Results The mean myopia prevalence in Fenghua was 84.5% (95% CI: 84.0–85.0%), and a slightly downward trend was found in myopia prevalence after 2019, but the change was not statistically significant (p = 0.078). The overall prevalence of myopia was 79.6, 85.2, and 86.1% in vocational high schools, general high schools, and key high schools, respectively, with statistically significant differences (p < 0.001). The prevalence of myopia among senior students in the vocational high school was significantly lower than that in the other two high schools. There’s no significant change in the overall prevalence of myopia (84.7% vs. 84.3%, p = 0.265) before and during the COVID-19 pandemic, and it remained statistically insignificant after stratifying by gender (male p = 0.207, female p = 0.918) or school types (vocational high school p = 0.112; general high school p = 0.299; key high school p = 0.393). Conclusion The prevalence of myopia among senior students in Fenghua is relatively high, and the COVID-19 pandemic has no significant impact on it. The prevalence of myopia among vocational high school students is lower than that of general high school and key high school. Attention should be paid to the effects of educational pressure on the prevalence of myopia among students.